Storytelling encyclopedia historical, cultural, and multiethnic approaches to oral traditions around the world (Oryx Press, 1997)
This is the first definitive reference work to address the substantive elements of oral storytelling, a form of communication that dates back to the dawn of humanity. It is an A to Z collection of over 700 entries covering such major storytelling elements as motifs, character types, tale types, place names, and creation mythologies and storytelling techniques of cultures around the world. Examples of subjects covered are the contributions of pioneering folklorists and mythologists such as: Franz Boas, Stith Thompson, and Joseph Campbell; descriptions of such well-known Western tales as Cinderella, the Greek myth of Persephone and Demeter, and the story of Exodus; as well as tales from Native American, African, and Asian cultures, including Indra and the Ants, tales of Anansi, the spider-trickster of the Ashanti, and the Cherokee Bear-man